Shamba shape up series 13 - Ep 10: Beef cattle, dryland crops, pests and diseases in tomatoes and climate literacy - Burra, Dharani Dhar; Ramírez Villegas, Julián Armando; Rottmann, Sophie; Galgallo, Diba; Murage, Paul; Campbell, David (2023)
"Shamba Shape Up" is a popular television show in East Africa that focuses on agricultural education and improvement. The show features a team of experts who visit different farms, providing practical demonstrations and advice to farmers on various aspects of agriculture, such as livestock rearing, crop cultivation, farm management techniques, and sustainable practices. It aims to educate and empower farmers with valuable information and skills to enhance productivity, increase yields, and improve their livelihoods. The program combines entertainment with education, using a reality TV format to engage viewers and encourage the adoption of better farming methods. This episode (part of Series 13) was broadcast during the 2023 long rains in Kenya and focuses on: (i) Beef cattle management; (ii) protecting tomatoes from pests and diseases; (iii) adapting to the changing climate, and (iv) choosing the best bean variety for dry areas.